FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEMISKINAN DI DESA JATI MULYO KECAMATAN JATI AGUNG KABUPATEN LAMPUNG SELATAN - Sasmita Padena Harahap; Kordiyana K. Rangga; Yuniar Aviati Syarief (Lampung University, 2020)
This research aims to determine poverty level, and factor related to the poverty level in Jati Mulyo Village, Jati Agung District, South Lampung Regency. This research was conducted in March-April 2018. Respondents were 70 households of poor families. Data were collected with a survey method using quantitative descriptive analysis and nonparametric statistical test (rank Spearman correlation). Results of this research showed that annual expenditure per capita was equivalent to the value of 233 kilograms of rice or the households were included in very poor category. Factors that were significantly related to poverty level were level of education and main occupation, while the number of family members and the age of the head of the household were not significantly related to poverty level.Key words: household, poor, poverty level